Desulfonative pd‐catalyzed coupling of aryl trifluoroborates with arylsulfonyl chlorides. (24th June 2016) - Wei, Zhen; Xue, Dazhong; Zhang, Haisheng; Guan, Jinyu
Abstract : A Pd‐catalyzedcross‐coupling of aryl trifluoroborates with arylsulfonyl chlorides has been successfully achieved. This transformation is a new method for the Suzuki–Miyaura‐type reaction of aryl trifluoroborates via the cleavage of C S bond, thus providing an alternative synthesis of biaryls. The reportedcross‐coupling reactions are tolerant to many common functional groups regardless of electron‐donating or electron‐withdrawing nature, making these transformations attractive alternatives to the traditionalSuzuki–Miyaura coupling approaches. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A Pd‐catalyzed cross‐coupling of aryl trifluoroborates with arylsulfonyl chlorides has been achieved. This transformation is a new method for the Suzuki–Miyaura‐type reaction of aryl trifluoroborates via the cleavage of C&bond;S bonds, thus providing an alternative synthesis of biaryls. The reported cross‐coupling reactions are tolerant to many common functional groups regardless of electron‐donating or electron‐withdrawing nature, making these transformations attractive alternatives to the traditional Suzuki–Miyaura coupling approaches.